2007
DOI: 10.1111/j.1540-8159.2007.00630.x
|View full text |Cite
|
Sign up to set email alerts
|

G‐CSF‐Induced Mobilization of CD34+ Progenitor Cells and Proarrhythmic Effects in Patients with Severe Coronary Artery Disease

Abstract: This is the first study showing that mobilization of CD34(+) EPCs is safe in patients with severe CAD. The accompanying leukocytosis did not appear proarrhythmic. Changes in P wave duration might be attributable to G-CSF therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…The reason for these findings is still unclear. A recent study evaluating G-CSF in myocardial infarction did not find evidence for an increase in classic systemic inflammatory markers [32]. Experimental data showed that G-CSF does not increase cardiac homing of progenitor cells [8].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The reason for these findings is still unclear. A recent study evaluating G-CSF in myocardial infarction did not find evidence for an increase in classic systemic inflammatory markers [32]. Experimental data showed that G-CSF does not increase cardiac homing of progenitor cells [8].…”
Section: Discussionmentioning
confidence: 97%
“…A second SPECT study was conducted on follow-up as well. Further details regarding patient population and study protocol have been published previously [32].…”
Section: Study Protocolmentioning
confidence: 99%
“…Several other works, while demonstrating that CSFs potently mobilized EPCs, failed to report significant improvements on the cardiovascular parameters under investigation [195][196][197][198]; specifically, left ventricular ejection fraction (LVEF), infarct size and overall left ventricular recovery did not benefit from G-CSF treatment in patients with acute myocardial infarction after reperfusion. Moreover, some authors argued about possible adverse effects [199,200]. The MAGIC trial is the archetype of the potential double-edged sword of CSFs usage: G-CSF therapy, followed by intracoronary infusion of mobilized cells, improved cardiac function and promoted angiogenesis in patients with myocardial infarction, but was dangerously associated with an increased rate of restenosis [201].…”
Section: Epcs and Cytokinesmentioning
confidence: 99%
“…The mechanisms by which EPCs mobilize and specifically home to areas of ischemia are highly complex and incompletely understood. They involve a range of pathways and stimulatory factors such as EPO (52), VEGF (53), and G-CSF (54) but it also appears that signals released from apoptotic endothelial cells are important for EPC recruitment to sites of vascular damage (55). Since the homing process is hypoxia-mediated, it is unsurprising that HIF-1α appears to be crucial for EPC recruitment to sites of vascular insufficiency (56).…”
Section: Endothelial Progenitor Cellsmentioning
confidence: 99%